Redefining luxury service with technology implementation: the impact of technology on guest satisfaction and loyalty in a luxury hotel. Issue 4 (28th January 2022) - Shin, Hyejo Hailey; Jeong, Miyoung
Abstract : Purpose: To explore the impact of luxury hotel brands' technologies on guests' perceived value enhancement and its consequences, this study aims to examine how task–technology fit (TTF) and luxury–technology fit (LTF) affect luxury hotel guests' perceived value enhancement, satisfaction and brand loyalty. Design/methodology/approach: A scenario-based online survey was conducted with existing and potential luxury hotel guests. The relationships among TTF, LTF, value enhancement, satisfaction and loyalty were examined using partial least square structural equation modeling. Moreover, the respondents were asked their preferred service agent (human staff vs technology) in a luxury hotel to further understand luxury hotel guests' perception toward technological services in a luxury hotel setting. Findings: The results reveal that both TTF and LTF have significant impacts on the luxury hotel's value enhancement, and the impacts of TTF and LTF on value enhancement are moderated by the guests' technology optimism. The findings of this study suggest that the luxury hotel brands must consider the fit between the image of their brand and the technology to increase guests' perceived value enhancement, satisfaction and loyalty. Research limitations/implications: Applying categorization theory, this study extended the concept of brand extension to technology implementation. The findings advance the current understanding of how technology affects luxury hotel consumers' perceived value enhancement, and how consumers' optimism influences the impacts of TTF and LTF on value enhancement. Practical implications: By examining the effects of TTF and LTF on luxury hotel guests' perceived value enhancement, this study would shed light on luxury hotel brands' technology implementation strategies. By understanding how TTF and LTF affect consumers' perceived value enhancement, luxury hotel brands will be able to better design their technology implementation plans. Originality/value: Even though luxury hotel brands are well known for offering high-level and personalized services through interpersonal interactions between employees and consumers, they have been actively implementing a variety of technologies to enhance guest experience and satisfaction. This study investigates the role of technological innovations in a luxury hotel setting. Particularly, this study examines how technologies improve guests' perceived value of a luxury hotel and lead to satisfaction and loyalty.